PREVALENSI KEJADIAN HYPERMETROPIA PADA MAHASISWA UNIVERSITAS MA CHUNG MALANG PADA BULAN JULI TAHUN 2024 Prevalence Of Hypermetropia In Students Of Ma Chung University Malang In July 2024 - Hendra Yuda; Joko Irawan; Kukuh Mujiono (CV. ALIM'SPUBLISHING, 2024)
Hypermetropia is a refractive disorder that affects the eye's focus on close objects and can affect academic activities. This study involved 125 students from Ma Chung University Malang, aged 17–24 years, to determine the prevalence of hypermetropia and explore factors that affect their visual health. Data collection was carried out through visual acuity examination using the Snellen chart and questionnaires related to visual habits and duration of gadget use. The results showed that 3.2% of respondents had hypermetropia. Most students (96.8%) used gadgets for more than two hours per day, with 91.2% of them doing so in a lying position, which can increase the risk of eye strain. In addition, symptoms such as blurred vision (58.4%) and eye fatigue (38.4%) were frequently reported. Other risk factors, such as lack of outdoor activities, also contributed to the decline in eye health. Education about healthy visual habits, such as the application of the 20-20-20 rule and regular eye examinations, is essential to prevent worsening of the condition. The results of this study are expected to be a basis for universities in increasing student awareness of the importance of maintaining eye health in the digital era.